Suppression of interdiffusion-induced voiding in oxidation of copper nanowires with twin-modified surface - Chun-Lung Huang (Nature Portfolio, 2018)
The Kirkendall effect can lead to detrimental voids in nanomaterials used in nanoelectronic devices, and its control remains elusive. Here, the authors introduce dense nanoscale twins in copper nanowires and modify their surface to prohibit Kirkendall void formation during nanowire oxidation.